Peran Pondok Pesantren Al-Aziziyah Dalam Membentuk Pendidikan Karakter Santri - Hariyanto, Totok; Hamid, Abdul (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2021)
Abstract The role of the pesantren in Indonesia status not only as an educational institution but also plays a role as a religious institution and not be separated from the figure of the Clerics, therefore the advice given by a religious figures be a decision. Students are required to always submissive and obedient to the Clerics of his and become an attraction for students, especially in a boarding school. The culture of the boarding school that makes a difference to the education system that are outside the boarding school as the value of simplicity, self-reliant, sincere and freedom. The activities of the students in their daily activities is from early morning until the evening that the koran the book together kyai so that students have a very strong character. Character education is a form of activity that it has an action that educate for the next generation. The goal of character education is the formation and improvement of individual self continuously and train the ability of self for the sake of reaching towards a better life. Character education can be implemented in an integrated manner, the learning can be implemented in keas and outside of the classroom, easy access can only get in at the boarding school, so the students or the students who are in boarding easy to control. Keywords : Role, Boarding School, Education, Character